Evaluasi Sistem Akuntansi Siklus Pendapatan pada PT. Unilab Perdana - Aries Wicaksono (Binus Business Review, 2013)
PT. Unilab Perdana is a company of environmental laboratories service provider. This study aims to evaluate the application of the accounting system in the revenue cycle, to identify the weaknesses and limitations of internal control, and to suggest improvements as needed. Research was carried out by using several methods. First, the method of data collection was conducted by the accounting system of internal control questionnaires revenue cycle. Second, the method of analysis was performed using the COSO internal control framework. The results obtained are accounting system in the revenue cycle applies to the company in general quite well, and accounting system in the company's revenue cycle has been partially implemented promptly and effectively, but there are still some things do not run effectively and efficiently.